2002
DOI: 10.1046/j.1365-2516.2002.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

MonoFIX‐VF, a new mono‐component factor IX concentrate: a single‐centre continuous‐infusion study

Abstract: MonoFIX-VF, a monocomponent factor IX concentrate, has replaced the use of Prothrombinex-HT as the treatment of choice for patients with factor IX deficiency in Australia. The haemostatic effect of MonoFIX-VF, administered by continuous infusion, was assessed in four subjects being treated for 10 bleeding episodes including five surgical procedures. MonoFIX-VF was found to be a safe and effective treatment for patients with haemophilia B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In 1992, a multicenter study by Goldsmith, et al [8], examined the use of AlphaNine Ò , a plasma-derived FIX concentrate, in 13 patients and found no adverse events and adequate haemostasis after surgery. Other studies have found similar results from both plasma-derived [9][10][11] and recombinant products [2,12]. Zakarija has reported a clear preference for plasma-derived factor in surgery because in her view, they provide more reliable control over factor levels and better control of bleeding [13].…”
Section: Introductionmentioning
confidence: 71%
“…In 1992, a multicenter study by Goldsmith, et al [8], examined the use of AlphaNine Ò , a plasma-derived FIX concentrate, in 13 patients and found no adverse events and adequate haemostasis after surgery. Other studies have found similar results from both plasma-derived [9][10][11] and recombinant products [2,12]. Zakarija has reported a clear preference for plasma-derived factor in surgery because in her view, they provide more reliable control over factor levels and better control of bleeding [13].…”
Section: Introductionmentioning
confidence: 71%
“…Literature review. Thirty‐five clinical studies were reviewed [10–44] (Table 1). Eight studies were considered to have reached level of evidence 2 and 27 studies up to level 3.…”
Section: Resultsmentioning
confidence: 99%
“…These studies comprised a total of 50 patients and 59 continuous infusion treatments (55 for major surgery) and provided evidence of an excellent hemostatic effect [35][36][37][38]46]. The initial factor IX (FIX) bolus of 12.4-155 IU was followed by infusion rates ranging between 1.7 and 8.6 IU/kg/h (median 3.9 IU/ kg/h) and aimed at maintenance FIX levels of more than 0.9 IU/ml in all studies but one that targeted FIX levels of 0.5-1.0 IU/ml.…”
Section: Continuous Infusion Of Factor IXmentioning
confidence: 99%